Retinoic Acid Downregulates HSPB8 Gene Expression in Human Breast Cancer Cells MCF-7 - Piccolella, Margherita; Cristofani, Riccardo; Tedesco, Barbara; Chierichetti, Marta; Ferrari, Veronica; Casarotto, Elena; Cozzi, Marta; Crippa, Valeria; Rusmini, Paola; Galbiati, Mariarita; Poletti, Angelo; Messi, Elio (Frontiers in Oncology, 2021)
Breast cancer (BC) is a serious and widespread disease for which different treatments have been developed. In addition to the classic therapies, the treatment with retinoic acid (RA) is still being clinically investigated. RA reduces cancer cells proliferation and migration, but its molecular mechanism of action is not clear. In tumor development, autophagy promotes cancer cell survival and prevents apoptosis. Small heat shock protein B8 (HSPB8) acts together with its co-chaperone BCL-2 associated athanogene 3 (BAG3) stimulating BC proliferation and migration. We analyzed whether direct correlations exist between RA and HSPB8 or BAG3 and how this may play a role in BC. We measured HSPB8 and BAG3 gene expression in MCF-7 BC cells and we analyzed the potential correlation between the antiproliferative and antimigratory effect of RA with the expression level of HSPB8. We found that in MCF-7 cells RA reduces both HSPB8 and BAG3 gene expression and it alters the mitotic spindle organization. Notably, the effects of RA on HSPB8 levels are exerted at both transcriptional and translational levels. RA effects are possibly mediated by miR-574-5p that targets the HSPB8 transcript. Our results suggest that therapeutic doses of RA can efficiently counteract the adverse effects of HSPB8 in BC progression.